MADUREZ OVÁRICA Y PROTEÍNAS DEL VITELO EN HEMBRAS DE TRIATOMA BARBERI USINGER, 1939 (HEMIPTERA: REDUVIIDAE, TRIATOMINAE) INFECTADAS EXPERIMENTALMENTE CON TRYPANOSOMA CRUZI (CHAGAS,1909) (PROTOZOA: TRYPANOSOMATIDAE) - Ramírez Cruz, Arturo; Nogueda Torres, Benjamín; Alejandre Aguilar, Ricardo; Martínez Morales, Imelda (Instituto de Ecología, A.C., 2005)
Triatoma barberi females were experimentally infected with Trypanosoma cruzi at the second ninfal instar. The effect of the infection on the ovaries and in yolk proteins eggs were evaluated. The morphological changes in ovaries during their maturation as well as electrophoretic patterns of the yolk proteins eggs in infected and uninfected females were studied. There was no significant difference in the growth patterns of the ovaries between both females groups. None difference in electrophoretic patterns of yolk proteins in the eggs between infected and uninfected females, was observed.